Species Diversity of Trees and Carbon Stock in Resort Pemerihan, Bukit Barisan Selatan National Park - Erly, Hasbiyan; Wulandari, Christine; Safe'i, Rahmat; Kaskoyo, Hari; Winarno, Gunardi Djoko (Jurnal Sylva Lestari, 2019)
Pemerihan Resort is a part of the Bukit Barisan Selatan National Park (BBSNP). The area of Pemerihan Resort is also part of a lowland tropical rainforest ecosystem with high carbon stocks and biodiversity levels. However, the biodiversity at Pemerihan Resort is threatened by human activities. The aim of this study is to understand species diversity of trees and the carbon stocks in Pemerihan Resort. The plots used include 5 clusters of the National Forest Inventory (NFI) plots within an area of 1 ha for each plot. Data collection was conducted by a census of all trees in the cluster plots and measurements of the diameters and heights of all trees. The measurements of the tree biomass were conducted by non-destructive sampling methods. The trees measured are 20 cm only. Species diversity of the trees was analyzed by Shannon-Whiener index. The carbon stock was analyzed using the Indonesian National Standard (SNI) referring to the Intergovernmental Panel on Climate Change (IPCC). The results showed that Pemerihan Resort is a mixed Dipterocarpaceae ecosystem and a type of normal forest. The dominance of Dipterocarpaceae is 38%. Pemerihan Resort has 611 of individual trees within 99 species and 38 families. The Diversity index (H') of Pemerihan Resort is 2.70. This is a moderately diverse and very stable environment. Tree carbon stock in Pemerihan Resort is 277.64 tons c/ha. The resort is included in the primary dryland category and High-Density forest (HK 3). The results of this study are useful as the basic data in conducting conservation efforts in the BBSNP area.Keywords: Carbon, diversity, tree, species, species, family